HYPER REALITAS SIMULAKRA TAGAR #2019GANTIPRESIDEN DALAM PEMILIHAN PRESIDEN INDONESIA 2019 - Dani Fadillah (Faculty of Social Sciences and Humanities Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2019)
This paper is aim to describe how a hashtag appearing in the dynamics of communication on social media is capable of creating a very massive mass movement in the real world. As well as troublesome rulers and authorities to set it up Because it considered a political charge that is in the hashtag could potentially provide a surge of turmoil that is great for the holder of the status quo of the political power of the homeland. By the election of the President of the Republic of Indonesia 2019 was presented with a viral hashtag on social media, the hashtags that were first administered twitted by prosperous Justice Party (Partai Keadilan Sejahtera) politician Mardani Ali Sera, raised the spirit of the masses The number is not minimal not to elect the general election which took place in April 2019. Even until the polls have done, the hashtag still has strong political magic to unite the opposition forces because the reunited was elected to become President of the Republic of Indonesia until 2022. This paper contains the results of qualitative research by making the idea of Jean Baudrillad about Simulacra, simulation, and artificial Phenomenon as his analysis knife. Here the author collects various literary sources in the different news media coverage of the hashtag #2019GantiPresiden then conduct a study of the messages that have a variety of information given to the hashtag Using the turbulent analytical knife of Jean Baudrillad above. Finally, the conclusion of this paper is necessary to fight massive efforts to resist the enormous surge of hashtags #2019GantiPresiden in the homeland in a variety of ways so that the focus is not more significant and to discuss the interests of Political authorities.